Development and initial evaluation of a novel 3D volumetric outlining system. Issue 1 (10th September 2015) - Bridge, Pete; Fielding, Andrew; Pullar, Andrew; Rowntree, Pamela
Abstract: Aim: The novel three-dimensional (3D) radiotherapy interactive outlining tool allows volumes to be created from a handful of points within axial, sagittal and coronal planes. 3D volumetric visualisation allows users to directly manipulate the resulting volume using innovative-sculpting tools. This paper discusses the development and initial evaluation of the software ahead of formal clinical testing. Materials and methods: User feedback was collated as part of the software development phase to ensure clinical suitability, define user training strategies and identify best practice. A loosely structured format was adopted with leading descriptive questions aiming to generate suggestions for improvements and initiate further discussion. Results: The four participants reported great satisfaction and value in being able to use all three planes for outlining, although orientation in 3D was evidently a problem. All participants felt that the software was capable of producing acceptable outlines rapidly and that the multi-planar capability allowed for improved outlining of the prostate apex. Findings: Mesh generation from a small number of points placed on a range of planes is a rapid and effective means of target delineation. Multi-slice volume sculpting and 3D orientation is challenging and may indicate a need for a paradigm shift in anatomy and computed tomography training.